A giant crocodile skull from Can Tho, named “Dau Sau”, represents the largest known saltwater crocodile (Crocodylus porosus) ever reported from Vietnam - Ziegler, Thomas; Tao, Nguyen Thien; Minh, Nguyen Trung; Manalo, Rainier; Diesmos, Arvin; Manolis, Charlie (Academia Journal of Biology, 2019)
We report on a large crocodile skull recovered from a river bank in August 2010 near Đầu Sấu Bridge, in An Binh, Ninh Kieu District, Cần Thơ Province, in southern Vietnam. As the skull from Cần Thơ, named “Đầu Sấu“ herein, is now deposited in the Vietnam National Museum of Nature, Hanoi, we reinvestigated the circumstances surrounding its discovery and provide exact measurements. Skull length (dorsal mid-point) is 70.7 cm. The morphological features confirm it is from a Saltwater crocodile (Crocodylus porosus), and not a Siamese crocodile (C. siamensis), which historically also occurred throughout the Mekong Delta of Vietnam. Skull measurements are compared with those of other large C. porosus skulls for which reliable estimates of total length are available. We also provide measurements of the prepared skull of “Lolong” (69.8 cm), a 6.17 m long C. porosus captured in the Philippines in 2011. On the basis of known skull length:total length ratios the crocodile from Cần Thơ is estimated to be 6.3-6.8 m long. The skull of Đầu Sấu is likely to have been buried for at least 100 years. We discuss the origin of the local name Đầu Sấu, which has traditional and cultural significance, and provide historical reports of crocodiles in the area. Đầu Sấu is smaller than the largest known C. porosus skull (76 cm), but is the largest ever reported from Vietnam, and one of the largest C. porosus known.